A implantação da escola primária graduada em Presidente Prudente-SP: as contribuições das professoras primárias (1925-1938) - Mariano, Jorge Luís Mazzeo (Universidade Federal de São Carlos, 2011)
This study aimed to show what was the involvement of primary teachers in Presidente Prudente for the deployment of the First Group School of the city between 1925 and 1938, within the context of the history of Presidente Prudente and the feminization of teaching. The main objective was to present and analyze the implementation of the First School Group and which (which) was (were) a (as) contribution (contributions) for construction of teachers' schooling and the building of primary school graduate in Presidente Prudente. To achieve this goal, we collected data in literature sources (books, theses, dissertations) and documentary sources (Reports, Books of Exams, journalistic material, etc.), plus the use of semi-structured interviews with eight individuals, using as support the theory of Oral History, with Paul Thompson as references. As a result more evident from the survey, we saw that the struggle of primary teachers has contributed to building the first primary school in the city, and we concluded that the strategy was unsuccessful struggle of the teachers of Presidente Prudente (tuned with the larger movement of feminization of teaching ), since the execution of his work was done in an exemplary manner, as indicated in the records of / from ex-students, and their performance outside the school walls, even if not brought to the attention of children, was added to all the practices that enabled these students to the same opportunity to chart a future different from that of their mothers and grandmothers had.
Keywords: Educação - história; Professoras; Feminização do magistério; Cultura escolar; Grupo Escolar; Presidente Prudente (SP); Professoras primárias; Cultura escolar; Primary teachers; Feminization of teaching; Scholar culture; Scholar group; Presidente Prudente; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO